Determining the rate of organizational maturity effect on the excellence of organization in Mobarakeh Steel Company - Iraj Soltani; Bahrami Reihaneh (مطالعات مدیریت بهبود و تحول, 2010)
maturity individually, procedurally and organizationally. Based on the studies conducted on organizational maturity at individual, procedural and organizational levels, a brief reference can be made to the following eight components taken as their signs and finding: 1. Sustainable Organizational Development, 2. Increased Productivity 3. Organizational Excellence and Development, 4. Employees Excellence, 5. Customer-Related Excellence, 6. Competitive Advantage, 7. Organizational Agility and 8. Increased Organizational Adaptability.The present work was conducted with the aim to measure the effect of organizational maturity on each of the above eight components at Mobarakeh Steel Company in 2010. In this study a statistical population comprising Mobarakeh Steel Company managers and professionals, 95 in number and a sample of 76 people were selected randomly based on the Morgan table. An inventory was developed to measure the effect of organizational maturity on maturity components. Having collected the data, the researcher analyzed the data using SPSS, Minitab, T-test and Tukey Posttest. The results indicated that the effect of individual maturity on organizational excellence was 47.86 %, the effect of procedural maturity 49.36 % and the effect oforganization maturity was 49.44 %. A study of reliability and internal validity of the test revealed that the reliability of the inventory was 0.921.